Racial resentment, crime concerns, and public attitudes toward defunding the police - Baranauskas, Andrew J. (Journal of ethnicity in criminal justice, 2022)
In the wake of highly publicized killings of unarmed citizens by police in the United States, calls to defund police departments have been particularly salient. This study seeks to determine the factors associated with attitudes toward defunding the police. Data from a national survey of American adults and generalized ordered logistic regression were used to examine two factors that may shape attitudes toward defunding police: racial prejudice and utilitarian concerns about crime. Racial resentment is the most consistent factor, being associated with adverse attitudes toward defunding police. Implications for research and policy are discussed.